2023
DOI: 10.1097/pcc.0000000000003337
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Nutrition Support in Latin American PICUs: The Nutrition in PICU (NutriPIC) Study

Santiago Campos-Miño,
Artur Figueiredo-Delgado,
Patricia Zárate
et al.

Abstract: Objectives: To characterize the nutritional status of children admitted to Latin American (LA) PICUs and to describe the adequacy of nutrition support in reference to contemporary international recommendations. Design: The Nutrition in PICU (NutriPIC) study was a combined point-prevalence study of malnutrition carried out on 1 day in 2021 (Monday 8 November) and a retrospective cohort study of adequacy of nutritional support in the week preceding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Our study on patients with CNI in our institution showed that 12% of the patients were diagnosed as underweight, 22.5% exhibited signs of chronic malnutrition, and 8% were classified as acute malnutrition ( Table 1 ). These results align with previously published reports of a ~20–30% prevalence of malnutrition in developed countries [ 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study on patients with CNI in our institution showed that 12% of the patients were diagnosed as underweight, 22.5% exhibited signs of chronic malnutrition, and 8% were classified as acute malnutrition ( Table 1 ). These results align with previously published reports of a ~20–30% prevalence of malnutrition in developed countries [ 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Existing malnutrition is not the only factor that influences clinical outcomes for these patients; the critical illness itself may increase metabolic demand in the early stages of the stress response, and nutrient intake may be limited. Thus, children admitted to a PICU are at a higher risk of worsening nutritional status and anthropometric changes, both of which could correlate with adverse clinical outcomes [ 21 , 22 , 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…My fourth Editor's Choice article comes from the Latin American Society of Pediatric Intensive Care (SLACIP) and is a point prevalence study of malnutrition and nutritional support in 41 PICUs in 13 Latin American countries on one day in 2021 (14). SLACIP identified 311 children on the day of study who, in general, had adequate enteral nutritional support but half the children did not receive recommended levels of calories and protein.…”
Section: What About Malnutrition and Nutrition Support In Latin Ameri...mentioning
confidence: 99%
“…Campos-Mino S, Figueiredo-Delgado A, Zarate P, et al; Nutrition Committee, Latin American Society of Pediatric Intensive Care (SLACIP): Malnutrition and Nutrition Support in Latin American PICUs: The Nutrition in PICU (NutriPIC) Study (14).…”
Section: What About Malnutrition and Nutrition Support In Latin Ameri...mentioning
confidence: 99%
See 1 more Smart Citation